If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -15 = 6x + 10 + -20 Reorder the terms: -15 + 6x = 6x + 10 + -20 Reorder the terms: -15 + 6x = 10 + -20 + 6x Combine like terms: 10 + -20 = -10 -15 + 6x = -10 + 6x Add '-6x' to each side of the equation. -15 + 6x + -6x = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 -15 + 0 = -10 + 6x + -6x -15 = -10 + 6x + -6x Combine like terms: 6x + -6x = 0 -15 = -10 + 0 -15 = -10 Solving -15 = -10 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -50y-25=15y-6 | | 8.3x+55.58=11.7x+54.68 | | -8x+12=-8x+5 | | -2(x+4)+3y=-5x+y-6 | | 6x+12-12=-6x | | 0-a=-2 | | 0.5x^2+2.5x-1.5=0 | | 3x^2+3x=180 | | -3x+7y*0=-21 | | 6x+12=3x-1 | | x*12x=2 | | -3x*0+7y=-21 | | -5-(15y-1)=2(7y-16y)-y | | 7(b+2)-2(b+10)-4b=5 | | 106-2=7b-7.4 | | f/10+5.9=1.8 | | 6(6v+6)+5=1+6v | | 12m-9-4m=15 | | -5*0+10y=-50 | | 5p+3p-8=p-1 | | 7(m+4)=2m+20 | | -5*0+10=-50 | | 3/4+4x=3/4 | | 2(x+4)=4(x-6) | | 12ln(x)=-6 | | 12lnx=-6 | | 2=-1+k/4 | | 3ln(4x)=-6 | | Y-1=-2x-12 | | 5x-1(2x+14)=10 | | .08m=3 | | x+(x+1)=2+(x+3) |